Pre-Operative Diclofenac Sodium Eye Drops Vs Intra-Operative Adrenaline Irrigation in Maintaining Mydriasis during Extracapsular Cataract Extraction - Mubashir Rehman, Zeeshan Tahir, Jehanzeb Khan, Imran Ahmad (Pakistan Journal of Ophthalmology, 2014)
Purpose: To compare the effectiveness of pre-operative diclofenac sodium eye drops with per-operative intraocular irrigation with adrenaline 1:1,000,000 (one in one million) solution in maintaining mydriasis during cataract surgery. Material and Methods: It was a randomized control trial and was conducted in the department of Ophthalmology, Khyber Teaching Hospital Peshawar from September 2010 to March 2011. 210 patients with senile mature cataracts were divided into two groups “A” and “B” with 105 patients in each group. Group “A” received pre-operative diclofenac eye drops for 24 hours and group “B” received per-operative irrigation with 1:1,000,000 of adrenaline solution. In all patients pupillary size was measured after cortical matter removal during extracapsular cataract extraction. Results: The mean age of patients in group “A” was 59.87 ± 6.54 SD years and in group “B” was 61.38 ± 6.30 SD. The mean pupillary size after cortical matter removal in group “A” was 7.0667 mm ± 1.78 SD while that in group “B” was 8.3371mm ± 1.94SD. The difference between the two was statistically significant after applying independent sample„t? test with p value of <0.000. Conclusion: Per-operative irrigation of adrenaline 1:1,000,000 solution keeps better pupillary size as compared to pre-operative diclofenac sodium for patients undergoing extracapsular cataract extraction, Key Words: Adrenaline, Extra capsular Cataract Extraction, Diclofenac sodium